Determination of Albumin in Urine by a Quartz Crystal Microbalance Label-Free Assay. (13th August 2017) - Theansun, Watcharinthon; Sripratumporn, Jittawat; Promptmas, Chamras
ABSTRACT: Albumin is a vital plasma protein in the control of osmotic pressure of human blood and is used as a screening marker for renal disease and Type I and Type II diabetic mellitus. A mass-sensitive immunosensor based on quartz crystal microbalance was used to determine microalbumin in urine on the antihuman albumin layer which was bonded to the protein A layer on the surface of a silver electrode. The analytical conditions were optimized for protein A and antihuman albumin on the electrode, and a calibration curve and the correlation between the microalbumin measured by the immunosensor and by a conventional method were evaluated. The results demonstrated that the optimal conditions for protein A coating on the silver electrode were 1 mg/ml and 2 h incubation at room temperature. The optimal conditions for antihuman albumin on the protein A-modified surface were 0.5 mg/ml at 2 h. The dose-response curve was linear from 0.0001 to 0.1 mg/ml. The comparison for the determination of microalbumin in urine by this method and a conventional approach showed good correlation with R 2  = 0.999 ( P  < 0.01). The receiver operating characteristic curve analysis showed 98.7% sensitivity, 100% specificity, and 1.00 for the area under the curve for the 0.02 mg/ml cutoff value. This system was label free and easy to use with high sensitivity and specificity. Therefore, the system may be used in place of commercial methods in the clinical laboratory.